Management of Student Welfare Services and Educational Stability of Undergraduates in Nigerian Universities - Fasanmi, Success Ayodeji (Studies in Learning and Teaching, 2025)
Transitioning from high school to university is one of the challenges undergraduates face when navigating their studies. This study assessed the management of welfare services and determined the level of students’ educational stability in Nigerian universities. The research was based on Maslow’s Hierarchy of Needs, providing insights into how students’ welfare needs impact on their educational stability. The study utilized descriptive research survey design. Two universities, namely Obafemi Awolowo University (OAU) and Oduduwa University (OUI) in Nigeria, were purposively selected for the study. A sample of 500 students was chosen from six out of the thirteen faculties in OAU and two out of the four colleges in OUI using a simple random sampling technique. Data were collected through questionnaires and analyzed using descriptive statistics. The study revealed that while clear policies guide the management of students’ affairs in the universities, there is inadequate engagement with the students by the authorities in managing students' welfare services, leading to student unrest at times. The study recommends the necessity for proper engagement and more responsive efforts to address the welfare needs of students by relevant authorities.